2022
DOI: 10.1021/acs.orglett.2c00190
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Azetidines through [3 + 1]-Cycloaddition of Donor–Acceptor Aziridines with Isocyanides

Abstract: The enantioselective [3 + 1]-cycloaddition of racemic donor–acceptor (D–A) aziridines with isocyanides was first realized under mild reaction conditions using a chiral N,N′-dioxide/MgII complex as catalyst, providing a facile route to enantioenriched exo-imido azetidines with good to excellent yield (up to 99%) and enantioselectivity (up to 94% ee). An obvious chiral amplification effect was observed in this system, and an explanation was elucidated based on the experimental investigation and X-ray crystal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…As illustrated in Scheme 3, with the assistance of the Dy( iii )/ L 3 -RaEt 2 complex, the carbon−carbon bond of 2,2′-diester aziridine is first cleaved to form azomethine ylide I , which adopts the E -configuration to reduce the steric hindrance between the aryl group and the sulfonyl group, and subsequently it is attacked by 2-isocyanoethylindoles. According to our previous work, 11 we deduce that the aforementioned addition from the Re -face of azomethine ylide I is more favourable to produce the nitrilium ion intermediate II . Then, the intramolecular Friedel–Crafts reaction occurs with the Re -face of the indole subunit, which affords the spiro intermediate III .…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…As illustrated in Scheme 3, with the assistance of the Dy( iii )/ L 3 -RaEt 2 complex, the carbon−carbon bond of 2,2′-diester aziridine is first cleaved to form azomethine ylide I , which adopts the E -configuration to reduce the steric hindrance between the aryl group and the sulfonyl group, and subsequently it is attacked by 2-isocyanoethylindoles. According to our previous work, 11 we deduce that the aforementioned addition from the Re -face of azomethine ylide I is more favourable to produce the nitrilium ion intermediate II . Then, the intramolecular Friedel–Crafts reaction occurs with the Re -face of the indole subunit, which affords the spiro intermediate III .…”
Section: Resultssupporting
confidence: 63%
“…7 As part of our continuing efforts in the development of asymmetric isocyanide-based cascade reactions, 7 c , d ,8 and chiral N , N ′-dioxide-based asymmetric catalysis, 9 we envisioned that the reaction of 2-isocyanoethylindoles with aziridines was probably feasible for the synthesis of this structure. 4 d ,10 As indicated in Scheme 1d, upon exposure to a chiral Lewis acid, donor–acceptor aziridine undergoes ring-opening to generate a transient azomethine ylide intermediate, 11 which is subsequently trapped by the isocyanide group of 2-isocyanoethylindole. The resulting electrophilic nitrilium ion species is attacked by the indole at the C3 position to construct the spiroindoline skeleton.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the systematic modification of N , N ′‐dioxides through alteration of the length of the linkage, still showed L 3 ‐RaPr 3 was the optimal ligand (see Table S2 in Supporting Information for details). Based on our previous researches on DA aziridines, [11d,f] the N ‐protected group of aziridine was examined. We found that the N ‐4‐trifluoromethylbenzene sulfonyl protected aziridine A1 produced the corresponding product C1b in 84 % ee after longer reaction time (see Table S4 for details).…”
Section: Resultsmentioning
confidence: 99%
“…In 2021, Luisi et al documented a sustainable mixed flowbatch approach for preparing functionalized NH-aziridines (112) from vinyl azides (109). The first part of the procedure was conducted under continuous flow conditions using CPME (cyclopentyl methyl ether) as the green solvent for obtaining a variety of 2H-azirines (110).…”
Section: Miscellaneous Intramolecular Aziridinationsmentioning
confidence: 99%
“…57 In 2022, Feng et al documented the ring enlargement of racemic donor-acceptor (D-A) aziridines (185) with isocyanides (186) catalyzed by a chiral N,N-dioxide (187)/Mg(II) complex, proceeding through ring opening via intermediates, such as 188, to yield enantioenriched exo-imido azetidines (189) (Scheme 34). 109 The preparation of 2-(2-oxoalkylidene)-1,3-oxazolidine derivatives (193) was described by Xu and co-workers in 2021 via the catalyst-free electrophilic ring expansion of N-unprotected aziridines (191) and the ketene CvO double bond of α-oxoketenes (192). 58 Products 192 were prepared in situ through microwave-assisted Wolff rearrangement of 2-diazo-1,3-diketones (190) (Scheme 35).…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%